PENGUKURAN CAPABILITY LEVEL TATA KELOLA DAN MANAJEMEN TI MENGGUNAKAN COBIT 5.0 PADA PT WELLCOMM RITELINDO PRATAMA - Aditya Pratama; Deborah Herby (JBASE - Journal of Business and Audit Information Systems, 2019)
In this study, researchers wanted to find out the level of information technology in the company through measuring the capability level of governance and information technology management at PT Wellcomm Ritelindo Pratama using the COBIT 5.0 framework. There are 3 research methods used, that is: observation, interview, and checklist. The first is to hold discussions about the goals of PT Wellcomm Ritelindo Pratama based on enterprise goals in COBIT 5.0. The second is mapping the company goals / enterprise goals to the IT goals of the company / it goals. Third is to enter into the process in COBIT 5.0. From the calculation results obtained from the process questionnaire is to determine the capability level of the process (target maturity) and whether the process can continue until the last level (5) or must stop at the initial level (1). The final step is to provide recommendations based on the final capability level and target capability level (next level). The results of measuring capability capability management and IT management using COBIT 5.0 PT Wellcomm Ritelindo Pratama, found several weaknesses that must be a concern of management in the future. The recommendations given are based on two targets: the target is carried out fully, so that the company can carry out each activity and complete it so that it can be said that the activity is carried out fully, and the target to be able to move up to the next level.